Imagining the Internet : communication, innovation, and governance - Mansell, Robin (Oxford : Oxford University Press, 2012)
Ch. 1: Introduction -- Ch. 2: Fast forwarding through the information society -- Ch. 3: Social imaginaries of the information society -- Ch. 4: Communication, complexity, and paradox -- Ch. 5: Communication systems in everyday life -- Ch. 6: Emergence and communication systems -- Ch. 7: Political firestorms in communication policy -- Ch. 8: Conclusion.